2019
DOI: 10.1073/pnas.1915569116
|View full text |Cite
|
Sign up to set email alerts
|

Hidden resources in the Escherichia coli genome restore PLP synthesis and robust growth after deletion of the essential gene pdxB

Abstract: SignificanceThe evolution of new metabolic pathways has been a driver of diversification from the last universal common ancestor 3.8 billion y ago to the present. Bioinformatic evidence suggests that many pathways were assembled by recruiting promiscuous enzymes to serve new functions. However, the processes by which new pathways have emerged are lost in time. We have little information about the environmental conditions that fostered emergence of new pathways, the genome context in which new pathways emerged,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
0
28
1
Order By: Relevance
“…An example is the recruitment of a promiscuous activity of 3‐phosphoglycerate dehydrogenase (SerA) to catalyze dehydrogenation of erythronate in a novel pathway assembled from promiscuous enzymes that restores PLP synthesis in a laboratory‐evolved strain of E. coli lacking PdxB (4‐phospherythronate dehydrogenase) (Fig. 6) [35]. The level of 3‐phosphoglycerate, the native substrate for SerA, is diminished in this strain due to a deletion in pgl that results in diversion of glyceraldehyde 3‐phosphate from glycolysis toward the pentose phosphate pathway and a point mutation in gapA that decreases the activity of glyceraldehyde 3‐phosphate dehydrogenase in the glycolytic pathway by fivefold.…”
Section: Iad Step 1: Neofunctionalizationmentioning
confidence: 99%
“…An example is the recruitment of a promiscuous activity of 3‐phosphoglycerate dehydrogenase (SerA) to catalyze dehydrogenation of erythronate in a novel pathway assembled from promiscuous enzymes that restores PLP synthesis in a laboratory‐evolved strain of E. coli lacking PdxB (4‐phospherythronate dehydrogenase) (Fig. 6) [35]. The level of 3‐phosphoglycerate, the native substrate for SerA, is diminished in this strain due to a deletion in pgl that results in diversion of glyceraldehyde 3‐phosphate from glycolysis toward the pentose phosphate pathway and a point mutation in gapA that decreases the activity of glyceraldehyde 3‐phosphate dehydrogenase in the glycolytic pathway by fivefold.…”
Section: Iad Step 1: Neofunctionalizationmentioning
confidence: 99%
“…Evolutionary repair experiments have been performed since the beginning of microbial experimental evolution. These original studies, like many current studies (e.g., [15]), focused on the evolution of novel metabolic and protein functions (e.g., [16][17][18]). Evolutionary repair experiments can provide insight into the mechanistic aspects of evolutionary biology and illuminate novel cell-biological phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to speculate that RsgA is also capable of dephosphorylating 4-phosphoerythronate The four-step serendipitous pathway feeds downstream of PdxB into the disrupted pathway and enable the bacteria to produce wild type levels of PLP (Fig. 2) (Kim et al 2019). The detailed characterisation of the suppressor mutants revealed that some strains mutations improved the oxidation of erythronate to 3,4-dihydroxy-2-oxobutyrate by the 3PG dehydrogenase SerA, which is usually active in serine biosynthesis (Fig.…”
Section: Alternative Metabolic Routes For Plp Biosynthesis In E Colimentioning
confidence: 99%
“…Recently, parallel lineages of the E. coli pdxB mutant strain have been evolved for up to 150 generations (Kim et al 2019 ). This adaptive laboratory evolution experiment led to the identification of a novel serendipitous pathway, which consist of the three promiscuous enzymes, an unknown phosphatase required for dephosphorylating 4PE, the 3-phospho-glycerate (3PG) dehydrogenase SerA and the homoserine kinase ThrB.…”
Section: De Novo Synthesis Of the B6 Vitamer Plpmentioning
confidence: 99%
See 1 more Smart Citation